2018
DOI: 10.1038/s41598-018-21972-z
|View full text |Cite
|
Sign up to set email alerts
|

Lightning initiation: Strong pulses of VHF radiation accompany preliminary breakdown

Abstract: We analyze lightning initiation process using magnetic field waveforms of preliminary breakdown (PB) pulses observed at time scales of a few tens of microseconds by a broad-band receiver. We compare these pulses with sources of narrow-band very high frequency (VHF) radiation at 60–66 MHz recorded by two separate Lightning Mapping Arrays (LMAs). We find that almost none of the observed PB pulses correspond to geo-located VHF radiation sources, in agreement with previous results and with the hypothesis that proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 33 publications
7
37
0
Order By: Relevance
“…In conclusion, using simultaneously sampled broadband FA and narrowband LogRF waveforms we have verified the hypothesis of Kolmašová et al () that classical IB pulses are systematically accompanied by VHF radiation and that most larger‐amplitude IB pulses are accompanied by VHF radiation. We have also found that the pulse amplitudes in E‐change data and in LogRF data are not correlated.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In conclusion, using simultaneously sampled broadband FA and narrowband LogRF waveforms we have verified the hypothesis of Kolmašová et al () that classical IB pulses are systematically accompanied by VHF radiation and that most larger‐amplitude IB pulses are accompanied by VHF radiation. We have also found that the pulse amplitudes in E‐change data and in LogRF data are not correlated.…”
Section: Discussionsupporting
confidence: 85%
“…Taking into account the results of Marshall et al (), who studied the first one or two classical IB pulses in two CG flashes and two intra‐cloud (IC) flashes and found significant VHF pulses occurring within the duration of each IB pulse, and findings of Kolmašová et al () who report that larger magnetic field IB pulses were systematically accompanied by VHF pulses in raw LMA (VHF) records, we first look for an occurrence of VHF pulses anytime within the duration of classical IB pulses. To be able to identify classical IB pulses, we downsampled the FA waveforms to 1 MHz to get rid of narrower pulses and subpulses.…”
Section: Analysis Of Waveformsmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical and chemical bases of intermolecular links of rocks are at the same time precursors of the occurring disturbances of these links, the cause of which is an increase in stresses in the rocks and subsequent elastic or residual deformations. On the assumption of the basics of intermolecular links, it is obvious that electromagnetic fields are an indicator, since crystal lattice deformations cause a change in the distances between atoms and quantummechanical fluctuations of the electron density of particles (molecules, atoms) [12][13][14][15][16][17][18][19][20][21][22][23][24]. The instantaneous distribution of the electric charge of the molecule, which corresponds to the instantaneous dipole moment of the molecule (or a higher order multipole moment), induces an electric multipole moment in another molecule.…”
Section: Geophysical Fields As Indicators Of Mechanical Processesmentioning
confidence: 99%